Analysis of research of strategies of positioning of leading universities of the world in the international information space - Shcherbak, Iryna (My University, 2020)
The research is devoted to the topical issue of positioning strategies of the world's leading universities, in particular the countries of Western Europe. A theoretical analysis of strategies for positioning the world's leading universities in the international information space on the basis of scientific papers on economics, sociology, organizational management, public administration, etc is done. This article focuses on the steps to model an effective positioning strategy as part of a university strategy that is subordinate in nature because it is designed to concretize and support the university-wide strategy and creates strategic advantages over competitors. The definition of the essence of strategies for positioning the leading universities of Western Europe in the international information space and the definition of external factors in the analysis of process strategies are considered. The need to universalize the higher education systems of Western Europe is found out, considering the nature of the new government. As a result of the study, it was found that for the successful operation of educational institutions, it is necessary to form and use positioning strategies properly. Therefore, according to the researcher, in order to achieve high rankings and remain competitive among other higher education institutions, in our time of rapid development, universities need to monitor changes in educational activities regularly and respond in a timely manner and eliminate shortcomings. After all, in today's world, education is a sphere of productive investment and one of the most influential levers of long-term action used by governments for economic development. The global education market is highly competitive, as education is increasingly becoming a means of advancing the country in the globalized labor market and the international market for new technologies.
Shcherbak I. Analysis of research of strategies of positioning of leading universities of the world in the international information space / I. Shcherbak // Порівняльна професійна педагогіка : наук. журнал : англо-українське вид. – Київ; Хмельницький, 2020. – С. 81–87.
Keywords: освіта, освітній простір, стратегії, позиціонування, провідний, університет, міжнародний, рейтинг, інформаційний простір; education, educational space, strategies, positioning, leading, university, international, rating, information space; образование, образовательное пространство, стратегии, позиционирование, ведущий, университет, международный рейтинг, информационное пространство